PENGARUH FAKTOR NON KEUANGAN DAN RASIO NILAI PASAR TERHADAP OPINI GOING CONCERN - Hadi, Fitria Handayani Fauziah; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of Public Accountant Office reputation, audit opinion of the previous years, opinion shopping and the ratio of market value to the opinion of going concern. The result of this research shows that partially the variable of opinion of the previous years has significant and positive influence to the opinion of going concern. Meanwhile, the Public Office Accountant reputation, opinion shopping and ratio of market value do not have any significant influence to the opinion of going concern.Keywords: Public Accountant Office (KAP) Reputation, Audit Opinion of the Previous Year, OpinionShopping and Ratio of Market Value.